Miliusa pumila (Annonaceae), a new species from S Thailand - Chaowasku,T. (Botanischer Garten und Botanisches Museum Berlin-Dahlem, 2015)
© 2014 BGBM Berlin-Dahlem. A new species, Miliusa pumila Chaowasku, is described and illustrated. It has been cultivated in Bangkok, Thailand, but was originally from S Thailand. Miliusa pumila can be principally distinguished from its most morphologically similar species, M. filipes Ridl., by the differences in leaf blade length, pedicel length, and number of stamens per flower. The new species can be mainly distinguished from M. thailandica Chaowasku & Kessler, its sister species previously elucidated by means of molecular phylogenetics, by the differences in leaf base, outer petal length, and inner petal size.